2004
DOI: 10.1175/1520-0426(2004)021<0921:coishd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Situ Humidity Data from Aircraft, Dropsonde, and Radiosonde

Abstract: Results are presented from the Measurement of Tropospheric Humidity (MOTH) Tropic and MOTH Arctic airborne field experiments, comparing a number of in situ humidity measurements. Good agreement is shown between the Total Water Content probe on board the C-130 aircraft, and the Vaisala RS90 and ''new'' Vaisala RS80 radiosondes; ''old'' Vaisala RS80 radiosondes and Vaisala RD93 dropsondes show the dry bias noted by others. An empirical correction for RD93 dry bias is presented and is shown to produce good result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…The dropsonde system (Vaisala RD93 [2]) records air pressure, temperature, relative humidity, altitude, wind speed and wind direction along with GPS coordinates while descending to the ground. The vertical resolution is about 8 m. The accuracy for temperature is given by the manufacturer as 0.2 K, for pressure 0.4 hPa, for relative humidity 2%, and for horizontal wind speed 0.5 m s and the respective harsh landing do not allow quantifying the near-surface temperature.…”
Section: Dropsonde Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The dropsonde system (Vaisala RD93 [2]) records air pressure, temperature, relative humidity, altitude, wind speed and wind direction along with GPS coordinates while descending to the ground. The vertical resolution is about 8 m. The accuracy for temperature is given by the manufacturer as 0.2 K, for pressure 0.4 hPa, for relative humidity 2%, and for horizontal wind speed 0.5 m s and the respective harsh landing do not allow quantifying the near-surface temperature.…”
Section: Dropsonde Systemmentioning
confidence: 99%
“…Data are of special interest due to different feedback mechanisms, like the interaction of the Arctic atmospheric boundary layer (AABL) with surfaces dominated by open water and ice, which differ strongly in terms of skin temperature and albedo. Therefore, dropsonde observations performed by aircraft [2] and radiosonde data obtained from ship and ice surfaces (e.g., during the Surface Heat Budget of the Arctic Ocean, SHEBA campaign [3]) and the Russian North Pole Drifting stations [4] are of great value for Arctic climate research.…”
Section: Introductionmentioning
confidence: 99%
“…Previous comparisons of PWV from RS‐90 sondes and MWRs at the ARM SGP and TWP sites have found that the radiosonde PW is consistently 6–8% drier for daytime soundings than for nighttime soundings (L. M. Miloshevich, personal communication, 2004). Other comparisons have also found a daytime dry bias of about 3–4% in the RS‐90 sondes [ Vance et al , 2004] and that this bias is due to solar heating of the air stream inside these sondes (J. Nash et al, Progress in improving upper air moisture measurements over the UK, preprints of 12th Symposium on Meteorological Observations and Instrumentation, American Meteorological Society, Long Beach, California, 2003).…”
Section: Intercomparisonsmentioning
confidence: 99%
“…This has been estimated as ±0.008 g/kg or ±8% (whichever is greater) for humidity mass mixing ratio, 0 < r < 20 g/kg, based partly on previous comparison with a cryogenically cooled mirror hygrometer [ Ström et al , 1994]. The aircraft humidity sensors were also compared with dropsonde and radiosonde sensors [ Vance et al , 2004]. Humidity profiles are derived from the Lyman‐α hygrometer throughout this study.…”
Section: Measurementsmentioning
confidence: 99%